Contractor Capability and Sustainable Project Outcomes: The Mediating Role of Life‑Cycle Cost Awareness and the Moderating Role of Regulatory Support - Muhammad Hamid Murtza (Journal of ICT, Design, Engineering and Technological Science, 2025)
This study investigates the influence of contractor capability on project performance and environmental sustainability, while ex‑amining the mediating role of life‑cycle cost awareness and the moderating effect of regulator support within Australia’s commercial and public building sectors. A quantitative cross‑sectional survey was conducted among construction professionals involved in commercial and public building projects. Using 185 valid responses, data were analyzed in STATA through reliability and validity assessment, correlation analysis, and structural modeling to test direct, mediating, and moderating relationships. The results indicate that contractor capability has a significant positive impact on both project performance (β = 0.611, p < 0.001) and environmental sustainability (β = 0.728, p < 0.001). Contractor capability also significantly predicts life‑cycle cost awareness (β = 0.693, p < 0.001), which in turn enhances project performance (β = 0.314, p < 0.001) and environmental sustainability (β = 0.341, p < 0.001). Regulator support strengthens life‑cycle cost awareness directly (β = 0.214, p = 0.001) and significantly moderates the relationship between contractor capability and life‑cycle cost awareness (β = 0.196, p = 0.006). Model fit indices demonstrate satisfactory fit (CFI = 0.947; RMSEA = 0.054). This study advances sustainable construction theory by integrating capability‑based and institutional perspectives and highlights life‑cycle cost awareness as a critical mechanism through which contractor capability translates into dual performance–sustainability outcomes. The findings provide actionable guidance for contractors and policymakers to improve project success and environmental outcomes through capability development and stronger regulatory support.